Glass : selected properties and crystallization - Schmelzer, J. (Walter de Gruyter GmbH & Co. KG, 2014)
This workdemonstrates how general features of glasses and glass transition are exemplified in different classes of glass-forming systems, such as silicate glasses, metallic glasses, and polymers. In addition, the wide field of phase formation processes and their effect on glasses and their propertiesis studied both from theoretical and experimental points of view.
Keywords: Glass.; elektronické knihy; electronic books